Policy Implications on Transport Infrastructure–Trade Dynamics: Case of Turkey - Duygu Şahan; Okan Tuna (Logistics)
Transportation has a mediating position in international trade formation and in the past few decades, Turkey has invested substantially in transport infrastructure to increase connectivity and integration in global transport networks. Still, limited research has been conducted to understand channels and scope of the transport infrastructure development impacts on foreign trade. The objective of this study is to evaluate short-run and long-run causal linkages between transport infrastructure, exports and imports in Turkey for the period between 1987–2019. An autoregressive distributed lag (ARDL) model is developed considering road and rail transport infrastructure components as well as information and communication technology (ICT) infrastructure as a complement to quality transport networks. Results suggest that a speedy road network serves as a locomotive in trade development whereas rail infrastructure can be beneficial if a holistic connectivity plan is developed in a long-term perspective to improve multimodal transportation under a comprehensive, sustained transport policy. Besides, benefits of transport infrastructure investment can be realized in favor of export promotion rather than import growth if a comprehensive policy is followed. In that way transport infrastructure investment would become a stronger instrument to accomplish export competitiveness.